Forward Prediction of Height‐Averaged Capillary Pressure–Saturation Parameters Using the BC‐vG Upscaler. Issue 3 (2nd May 2013) - Cheng, C.-L.; Perfect, E.; Mills, R.T.
Abstract : There is ongoing interest in approaches for upscaling point (e.g., pixel or voxel scale) measurements of soil hydraulic properties to predict column‐scale behavior in the laboratory, or even field‐scale processes. We have developed the BC‐vG Upscaler for estimating the height‐averaged capillary pressure–saturation relationship, θ ¯ ( h ¯ ), for a given porous medium based on equations used in the TrueCell program. Whereas TrueCell inversely estimates point Brooks and Corey (BC) equation parameters from θ ¯ ( h ¯ ) data, the BC‐vG Upscaler uses point BC parameters as inputs for the forward prediction of height‐averaged van Genuchten (vG) parameters. The BC‐vG Upscaler was verified using previously published, independent point and height‐averaged capillary pressure–saturation data sets for silica sand. The capability of the BC‐vG Upscaler was demonstrated in three separate applications. The first showed how the program can be used to predict height‐averaged vG equation parameters using three different relationships between n and m . The second explored the effects of varying column height on the predicted vG parameters for a hypothetical porous medium. The third used the BC‐vG Upscaler to predict height‐averaged vG parameters for a 50‐cm‐tall column based on previously published point BC parameters for a wide range of porous media. The BC‐vG Upscaler is available free upon request. It should prove useful for converting point BC parameters into height‐averaged vG parameters suitable for inclusion in numerical models for simulating variably saturated flow. The program could also be used to develop new scale‐dependent relationships between the parameters of the BC and vG equations.